Multi-Objective Optimization of Nano-Silica Modified Cement-Based Materials Mixed With Supplementary Cementitious Materials Based on Response Surface Method - Zhang, Xiuzhi; Lin, Liming; Bi, Mengdi; Sun, Hailong; Chen, Heng; Li, Qinfei; Mu, Ru (Frontiers in Materials, 2021)
This paper investigates the effect of supplementary cementitious materials (SCMs) on fresh and mechanical properties of nano-silica modified cement-based materials (NSMCBM) based on response surface method (RSM). Among them, three kinds of SCMs namely fly ash (FA), ground granulated blast-furnace slag (GGBFS) and silica fume (SF) were selected and Box-Behnken Design method (BBD) was used to design mix proportion. Besides, quadratic term model was used to describe the relationship between independent variables and responses including fluidity, yield stress, plastic viscosity, thixotropy, 3d, 7d, 28d and 56d compressive strength. Based on quadratic term model, response surface of every responses was plotted to understand the effect of SCMs on the dependent variables. Results showed that FA had significant effect on fluidity and thixotropy while three kinds of SCMs had extremely significant effect on plastic viscosity. Besides, SCMs had negative effect on compressive strength but FA increased the 56d strength. Response surface plot showed that the addition of some SCMs decrease the fluidity and rheology of NSMCBM to be comparable with the paste without SCMs and nano-silica (NS). Meanwhile, NS complemented the reduction of compressive strength caused by SCMs. Thus, the combination of SCMs and NS could improve both fresh and mechanical properties. At last, multi-objective optimization was utilized to optimize the proportion of SCMs considering the interaction between SCMs to achieve desirable parameters.